Review of West-Palaearctic Hebridae with description of a new species and redescription of Hebrus fulvinervis (Hemiptera: Heteroptera) - Kment, Petr; Jindra, Zdeněk; Berchi, Gavril Marius (Zootaxa, 2016)
A review of the West-Palaearctic Hebridae and their distribution is given, including two genera and 21 species-group taxa (18 species and 3 subspecies). A new species, Hebrus (Hebrus) atlas sp. nov. (Hemiptera: Heteroptera: Hebroidea: Hebridae: Hebrinae), is described from Morocco and is the first micropterous species of Hebrus s. str. in the Palaearctic Region. The species Hebrus fulvinervis Horváth, 1929, not recorded since its original description, is rediscovered, redescribed, and its species status is confirmed. Based on the morphological characters, H. fulvinervis is considered closely related to H. ruficeps Thomson, 1871, and transferred to the subgenus Hebrusella Poisson, 1944. Remarks on the morphology of Hebrus syriacus Horváth, 1896 are provided and its placement in the subgenus Hebrus s. str. is confirmed. The following new or confirmed distribution records are provided: Hebrus acutiscutatus Brown, 1951 from Israel, H. fulvi-nervis from Bulgaria, H. jeanneli djaneti Poisson, 1953 from Morocco, H. montanus Kolenati, 1857 from Israel and Romania, H. pusillus arabicus Linnavuori, 1971 from Iran (Hormozgan) and Oman, H. pusillus pusillus (Fallén, 1807) from Greece and Lithuania, H. syriacus from Cyprus, and H. vaillanti Poisson, 1953 from Morocco. Several corrections concerning type localities, type material and depositories are also provided.